Magnon-assisted tunnelling in van der Waals heterostructures based on CrBr3 - Ghazaryan, D.; Greenaway, M.T.; Wang, Z.; Guarochico-Moreira, V.H.; Vera-Marun, I.J.; Yin, J.; Liao, Y.; Morozov, S.V.; Kristanovski, O.; Lichtenstein, A.I.; Katsnelson, M.I.; Withers, F.; et al. (Springer Nature, 2018)
Van der Waals heterostructures, which are composed of layered two-dimensional materials, offer a platform to investigate a diverse range of physical phenomena and could be of use in a variety of applications. Heterostructures containing two-dimensional ferromagnets, such as chromium triiodide (CrI3), have recently been reported, which could allow two-dimensional spintronic devices to be developed. Here we study tunnelling through thin ferromagnetic chromium tribromide (CrBr3) barriers that are sandwiched between graphene electrodes. In devices with non-magnetic barriers, conservation of momentum can be relaxed by phonon-assisted tunnelling or by tunnelling through localized states. In contrast, in the devices with ferromagnetic barriers, the major tunnelling mechanisms are the emission of magnons at low temperatures and the scattering of electrons on localized magnetic excitations at temperatures above the Curie temperature. Magnetoresistance in the graphene electrodes further suggests induced spin–orbit coupling and proximity exchange via the ferromagnetic barrier. Tunnelling with magnon emission offers the possibility of spin injection.